The The Profile of Syphilis and Human Immunodeficiency Virus (HIV) Infection in Street Children at Home Shelter of Social Services in Medan - Gemala, Rabiah; Hutapea, Richard; Nadeak, Kristina (International Journal of Innovative Research in Medical Science, 2019)
Background: Syphilis and HIV infection have similar ways of transmission, therefore these infections can affect similar patient groups and co-infection is common. Street children are very susceptible to sexual transmitted infection and HIV due to their lack of protection and care from their parents and also they often use addictive substances. Aim: To find out the profile of syphilis and HIV infection in street children at home shelter of social services in Medan. Subject and method: This was a cross-sectional descriptive study involving 50 street children at home shelter of social services in Medan. We did serologic examinations (VDRL/TPHA and HIV) to all of the subjects. Results: In this study, from 50 subjects, most of them were 14 – 18 years old (86.0%), male (98.0%) with the highest level of education was junior high school (52.0%). There were three children (6.0%) with syphilis, all of them were 14 – 18 years old, males with the highest level of education was junior high school. Five children (10.0%) were positive HIV, all of them were males and 14 – 18 years old. There was one child (2.0%) with syphilis and HIV co-infection. Conclusion: Most of street children in home shelter of social services in Medan were 14 – 18 years old, male, with the highest level of education was junior high school. Proportion of syphilis in this study was 6.0% and HIV 10.0%. Syphilis and HIV co-infection was found 2.0% in this study.